Endophytic bacteria from Jatropha curcas suppress Meloidogyne spp. and promote eggplant growth under greenhouse conditions - Yousif, Ahmed Ibrahim Alrashid; Roswanjaya, Yuda Purwana; lbrahim, Elrasheed Siddig Libs; Munif, Abdul; Pradana, Ankardiansyah Pandu; Ahmed, Naseer (Acta Biologica Szegediensis, 2026)
In recent years, pesticide use has increased, posing risks to humans, the environment, and other life forms. This study evaluated the potential of endophytic bacteria isolated from Jatropha curcas L. to promote growth and suppress Meloidogyne spp. in eggplant (Solanum melongena L.) under greenhouse conditions. Three isolates, FJS23 (Pseudomonas sp.), SJS54 (Micrococcus sp.), and RJS175 (Pseudomonas sp.), were selected based on biosafety and biochemical screening and identified using 16S rRNA gene sequencing. Before application, bacterial suspensions were adjusted to OD600 = 1.0 and applied as root dips followed by soil drenching, either singly or in two- and three-isolate combinations. Plant growth and nematode parameters were assessed 40 days after nematode inoculation. All treatments significantly enhanced plant growth compared with the control (DMRT, α = 0.05; n = 7). Isolate SJS54 (Micrococcus sp.) produced the tallest plants (60.10 cm), while the combination FJS23 (Pseudomonas sp.) + SJS54 (Micrococcus sp.) resulted in the highest shoot fresh weight (93.30 g), dry weight (17.91 g), and leaf number (20.5). Nematode infestation and root galling were markedly reduced by all treatments compared with the control (131.5 galls root-¹ and 3.046 galls g-¹ root). Notably, SJS54 (Micrococcus sp.) reduced gall formation to 1.25 galls root-¹ and 0.015 galls g-¹ root, representing a >99% reduction relative to the control (DMRT, α = 0.05; n = 7). These results demonstrate that J. curcas-derived endophytes, particularly SJS54 (Micrococcus sp.) and its combinations, can effectively promote plant growth and suppress root-knot nematodes, offering a sustainable alternative to chemical nematicides for eggplant production.